Cultures and Globalization The Cultural Economy - Anheier, Helmut K; Anheier, Helmut K (SAGE Publications, 2008)
The world's cultures and their forms of creation, presentation and preservation are deeply affected by globalization in ways that are inadequately documented and understood. The Cultures and Globalization series is designed to fill this void in our knowledge. In this series, leading experts and emerging scholars track cultural trends connected to globalization throughout the world, resulting in a powerful analytic tool-kit that encompasses the transnational flows and scapes of contemporary cultures. Each volume presents data on cultural phenomena through colourful, innovative information graphics to give a quantitative portrait of the cultural dimensions and contours of globalization. This second volume The Cultural Economy analyses the dynamic relationship in which culture is part of the process of economic change that in turn changes the conditions of culture. It brings together perspectives from different disciplines to examine such critical issues as: ? the production of cultural goods and services and the patterns of economic globalization ? the relationship between the commodification of the cultural economy and the aesthetic realm ? current and emerging organizational forms for the investment, production, distribution and consumption of cultural goods and services ? the complex relations between creators, producers, distributors and consumers of culture ? the policy implications of a globalizing cultural economy By demonstrating empirically how the cultural industries interact with globalization, this volume will provide students of contemporary culture with a unique, indispensable reference tool.